KEKERASAN PADA ANAK (child abuse) DI PENDIDIKAN ANAK USIA DINI MOJOKERTO - Tripeni, Tripeni (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2013)
Child abuse is a repeating violence assault both phisically or emosionally, through urges, uncontrolled corporal punishment, obvious degradation and permanent ridicule and sexual violence. The purpose of this study was to determine child abuse in Early Childhood Education Tarbiyatush Shibyan Mojokerto.The research used the survey. Sample of this study were 51 respondents, variables studied were, number of children, maternal age, occupation, education, family economics and child abuse. The sampling technique used was simple random sampling is random sampling is lacking.The results showed that families with higher economic status 6 (11.6%) experienced violence, while families with low economic status 21 (15.4%) experienced violence.Thus expected to promote other forms of child abuse. Parents are not expected to do violence on children, because it can effect their development. Hence, it is vital to be able to approach the victims privatelly or through sosial approach. As also it is important that society participates by reporting any child abuse case and be aware of the act of violence.Keywords: Child, abuse